Substandard and falsified medicines in Africa: healthcare systems challenges, supply chain issues, regulatory challenges and strategies to increase access to quality medicines - Chabalenge, Billy; Sahota, Tarsem; Ermolina, Irina; Tanna, Sangeeta (Frontiers in Pharmacology, 2025)
Africa is a unique continent due to high disease burden for both communicable and non-communicable diseases, attracting large-scale distribution of medicines to tackle public health issues. This poses several challenges for the healthcare systems, particularly concerning the circulation of substandard and falsified medicines. The widespread of substandard and falsified medicines causes adverse health effects on patients and contributes to millions of deaths annually. This review explores how health systems in Africa, supply chain issues and regulatory environment affect the circulation of substandard and falsified medicines. A narrative review was conducted drawing information from academic publication, official reports and other grey literature between January 2014 and October 2025 focusing on substandard and falsified medicines, health systems, supply chain and regulatory issues in Africa. Health system challenges in Africa include uneven geographical distribution of health facilities, medicines stockouts, increased costs of medicines purchased from private healthcare facilities and inadequate health financing. These factors increase out-of-pocket expenditure on patients and drive the poor majority of Africans to source cheaper medicines from unregulated markets, thereby increasing the likelihood of consuming substandard and falsified medicines. Supply chain issues include a lack of industrialisation to meet the medicine demand, a lack of support to local logisticians, poor forecasting, and over-dependence on imports, complicating the supply of quality medicines. The complexity of the supply chain system creates numerous opportunities to disrupt the supply of quality and safe medicines, making it easy for substandard and falsified medicines to reach the patient. Medicines regulation in Africa also suffers several challenges including limited well-functioning regulatory systems, inadequate staffing levels and a lack of analytical technologies for fast screening of substandard and falsified medicines. The review further provides recommendations and priority areas that should be considered to strengthen health systems, supply chains and regulation of medicines in Africa to reduce the prevalence of substandard and falsified on the continent.